Unravelling The Link Between Sars-cov-2 Mutation Frequencies, Patient Comorbidities, And Structural Dynamics - Amirah Azzeri; Nurul Azmawati Mohamed @ Abd Aziz; Saarah Huurieyah Wan Rosli; Muttaqillah Najihan Abdul Samat; Zetti Zainol Rashid; Muhamad Arif Mohamad Jamal; Muhammad Zarul Hanifah Md Zoqratt; Muhammad Azamuddeen Mohammad Nasir; Harpreet Kaur Ranjit Singh; Liyana Azmi (Plos One, 2024)
Indexed by WOS/Scopus/ERA